A 2007 Social Accounting Matrix (SAM) for Lesotho - van Seventer, Dirk (International Food Policy Research Institute, 2014)
A 2007 Social Accounting Matrix (SAM) for Lesotho is constructed using data that available during the second half of 2011. The SAM provides a detailed representation of the Lesotho economy. It separates 24 activities and 23 commodities; labor is disaggregated by 3 broad skill groups (high, medium and low); and households into 6 groups based on the rural/urban and income earning status of the household head. The SAM is a useful database for conducting economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.